2021
DOI: 10.1016/j.xnsj.2021.100072
|View full text |Cite
|
Sign up to set email alerts
|

The influence of comorbidities on the treatment outcome in symptomatic lumbar spinal stenosis: A systematic review and meta-analysis

Abstract: Background: Lumbar spinal stenosis (LSS) affects mainly elderly patients. To this day, it is unclear whether comorbidities influence treatment success. The aim of this systematic review and meta-analysis was to assess the impact of comorbidities on the treatment effectiveness in symptomatic LSS. Methods:We conducted a systematic review and meta-analysis and reviewed prospective or retrospective studies from Medline, Embase, Cochrane Library and CINAHL from inception to May 2020, including adult patients with L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…15,18,28 Possibly, worse baseline disability may be related to smaller improvement in disability after surgery as a continuous outcome, 52,64 but not as MCID. 54,65 Medical comorbidities are known to increase the risk of postoperative complications, 71,72 however, their effect on longer-term spinal surgery outcomes is less clear. 19,73 We found very low-quality evidence supporting significant associations between present comorbidities and smaller benefit from surgery in terms of reduction in pain, but not disability (low-quality).…”
Section: Health-related Predictorsmentioning
confidence: 99%
“…15,18,28 Possibly, worse baseline disability may be related to smaller improvement in disability after surgery as a continuous outcome, 52,64 but not as MCID. 54,65 Medical comorbidities are known to increase the risk of postoperative complications, 71,72 however, their effect on longer-term spinal surgery outcomes is less clear. 19,73 We found very low-quality evidence supporting significant associations between present comorbidities and smaller benefit from surgery in terms of reduction in pain, but not disability (low-quality).…”
Section: Health-related Predictorsmentioning
confidence: 99%
“…15,18,28 Possibly, worse baseline disability may be related to smaller improvement in disability after surgery as a continuous outcome, 52,64 but not as MCID. 54,65 Medical comorbidities are known to increase the risk of postoperative complications 71,72 ; however, their effect on longerterm spinal surgery outcomes is less clear. 19,73 We found very low-quality evidence supporting significant associations…”
Section: Limitationsmentioning
confidence: 99%
“…Microendoscopic procedures such as unilateral laminectomy bilateral decompression (ULBD) or interspinous decompression devices such as X-STOP are introduced as an alternative to laminectomy. 8 A study done to compare the outcome of laminoforaminotomy vs. laminectomy in lumbar spinal stenosis in terms of claudication distance showed that 15.2% of laminectomy and 5.6% of laminoforaminotomy patients have a poor outcome, while 75.8% and 83.3% have a good outcome in laminectomy and laminoforaminotomy group, respectively. Those having excellent outcomes were 9.1% in the laminectomy group and 11.1% in the laminoforaminotomy group.…”
Section: Introductionmentioning
confidence: 99%